Civil security in CEMAC States - (:unkn) unknown (My University, 2015)
Civil security in the Economic and Monetary Community of Central African States, whose main objective is the protection of persons, goods and the environment, is faced with different contemporary risks and crisis. The quite widespread vulnerability and disregard in this part Africa, heightened by unabating constraints caused by poverty and weak institutional frameworks exposes them to deadly and disastrous disaster consequences.The situation is alarming; yet it is hardly a priority on government policies, both in the internal policies of each CEMAC member state and at the sub regional level.The various actions initiated here and there at the institutional, legal and human levels are still timid. One of the major reasons is that civil security in this part of the continent is relatively young and divided amongst a multitude of actors confronted permanently with dramatic events and the complexity of the crisis.Moreover, it needs more than other fields, to be specified and consolidated. The major problem which is developed in the thesis is then, how to face the challenging issues, avoid and prevent crisis in an environment where the vulnerabilities are enhanced by poverty? In other words, what happens during a disaster in a context where the ability to preempt and to manage risks is particularly limited?From the legal approach, as well as interdisciplinary, we have revealed the limits of the classical model which civil security systems of CEMAC states basically depend on, to the detriment of other relevant models of risk management(taking into account vulnerability and resilience) which feature on the law of civil security of these states just as an alignment.The reality is clear and brutal: risks and disasters are omnipresent in the CEMAC zone; this is the shadow overbearing the present and the future. This gloom reveals the absence of development of the sub region and the poor dissemination of technology and knowledge. Faced with this unprecedented situ
Keywords: African Research